2021
DOI: 10.2147/jir.s287346
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A Receptor Agonist Polydeoxyribonucleotide Alleviates Interstitial Cystitis-Induced Voiding Dysfunction by Suppressing Inflammation and Apoptosis in Rats

Abstract: Background Interstitial cystitis (IC) is a chronic disorder that indicates bladder-related pain or discomfort. Patients with IC often experience urination problems, such as urinary frequency and urgency, along with pain or discomfort in the bladder area. Therefore, new treatments based on IC etiology are needed. Polydeoxyribonucleotide (PDRN) is a biologic agonist of the adenosine A 2A receptor, and PDRN has anti-inflammatory effect and inhibits apoptosis. In the current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, confounding results exist regarding the influence of activation or suppression of P1 receptors, specifically adenosine receptor A2a, on inflammatory response and bladder overactivity. Yang et al reported that inhibition of adenosine A2a receptors with ZM241385, a selective A2a receptor antagonist, significantly alleviated bladder overactivity and hyperalgesia in CYP-treated animals by reducing the sensitivity of TRPV1 in DRG neurons [ 128 ], while Ko et al showed that activation of adenosine A2a receptor with polydeoxyribonucleotide (PDRN), an A2a receptor agonist, improved voiding dysfunction and reduced inflammation and apoptosis [ 129 ]. Interestingly, anti-inflammatory effects of PDRN have previously been demonstrated in animal models of various diseases, such as ischemic colitis, gastric ulcers, and Achilles tendon injury [ 130 , 131 , 132 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, confounding results exist regarding the influence of activation or suppression of P1 receptors, specifically adenosine receptor A2a, on inflammatory response and bladder overactivity. Yang et al reported that inhibition of adenosine A2a receptors with ZM241385, a selective A2a receptor antagonist, significantly alleviated bladder overactivity and hyperalgesia in CYP-treated animals by reducing the sensitivity of TRPV1 in DRG neurons [ 128 ], while Ko et al showed that activation of adenosine A2a receptor with polydeoxyribonucleotide (PDRN), an A2a receptor agonist, improved voiding dysfunction and reduced inflammation and apoptosis [ 129 ]. Interestingly, anti-inflammatory effects of PDRN have previously been demonstrated in animal models of various diseases, such as ischemic colitis, gastric ulcers, and Achilles tendon injury [ 130 , 131 , 132 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous papers have demonstrated that adenosine A 2Ar activation prevents ROS generation, also reducing inflammation and the apoptotic process [24,25]. PDRN, which is recognized as an A 2Ar agonist, showed several properties-including antioxidant, anti-apoptotic and anti-inflammatory ones-in several pre-clinical in vivo disease models, such as airway inflammation, cerebral ischemia, interstitial cystitis, acute lung injury, and ischemic colitis [26][27][28][29][30]. Moreover, a previous clinical trial demonstrated that PDRN eye drops stimulated corneal epithelium regeneration, thus supporting the hypothesis that it could be used for the treatment of corneal diseases [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Antiapoptotic Bcl-2 can inhibit the permeability changes of the outer mitochondrial membrane caused by Bax to prevent the release of cytochrome C into the cytoplasm, thereby inhibiting the occurrence of apoptosis [ 41 ]. In previous studies, it was found that CYP can cause urothelial cell apoptosis by upregulating the ratio of Bax/Bcl-2 [ 42 ]. Caspase-8 participates in apoptosis induced by the death receptor pathway [ 43 ].…”
Section: Discussionmentioning
confidence: 99%